Green Information Technologies in Business Operations - Arshi Naim (Periodica Journal, 2021)
Climatic changes have raises the concern worldwide and countries are conducting summits to solve and prevent global warming. Information Technologies have been playing the great roles in keeping the objectives of preserving environment and one of the techniques is to apply green computing. Green computing is also called as Green Information Technologies (GIT) which is the practice and procedures of using computing and other technological resources in a responsible and environmentally friendly manner. The focus of GIT is to decrease the use of hazardous materials, reduce usage of energy, increase profit maximization and create the awareness of advantages of recyclability or biodegradability of the computer trash. This paper presents the theoretical background of GIT, its roles and advantages for preserving climate. Also, this paper presents qualitative analysis on advantages and challenges of using GIT in business operations (BPO). These advantages are presented through very short instances and cases for the applications of GIT in BPO. GIT includes new services and products with optimum efficiency andpossible options towards energy saving so it provides the best way to keep the environment clean and healthy without trading off the use of technologies.
Keywords: Green Computing; GIT; Recycle; Computer Trash